Tradisi Larangan Nikah Ngalor Ngulon di Daerah Purwoharjo Banyuwangi Perspektif Teori Sistem Jasser Auda - Badrut Tamam; Risna Ismawati (MAHAKIM Journal of Islamic Family Law, 2022)
The purpose of this research is to find out the background factors and description of the tradition of prohibiting Ngalor Ngulon marriage in Purwoharjo Village from the Perspective of Jassir Auda's System Theory. This research method uses qualitative field research with a conceptual approach using Jassir Auda's systems theory concept. The research data was generated through direct interviews with the people of Purwoharjo Village, Purwoharjo District, Banyuwangi Regency as the research location. The conclusion of this study is that the Ngalor Ngulon Marriage Prohibition tradition is prohibited in Purwoharjo Village due to several factors, namely habit or customs, lack of religious knowledge, belief, and social structure. Based on Jasser Auda's view, the purpose of Islamic law must be universal so that Islamic law can be accepted anytime, anywhere, and in all circumstances, with the aim of the common good rather than individuals. A system for dealing with problems must be in accordance with the goals of Islam itself. Referring to the Ngalor Ngulon Marriage Prohibition tradition, it can be preserved by removing fasid or harmful elements in the custom. This is because this tradition is a custom or custom of Purwoharjo Village which cannot be simply erased. This tradition also does not necessarily prohibit marriage, but only in certain directions, namely Ngalor Ngulon.